Comparative analysis of blockchain consensus algorithms from Shariah perspective / Tasneem Darwish … [et al.] - Darwish, Tasneem; Abu Bakar, Kamalrulnizam; Matsuda, Gen; Aliyu, Ahmed; Abdullah, Abdul Hanan; Ismail, Abdul Samad; Yusof, Ahmad Fadhil; Raja Mohd. Radzi, Raja Zahilah; Mohamad, Mohd Murtadha; Idris, Mohd Yazid; Ismail, Zuhaimy; Che Yaacob, Ahmad (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2020)
Blockchain provides a distributed digital ledger platform for not only cryptocurrencies but also many other distributed applications. Blockchain platforms workflow and performance are controlled by the used consensus algorithms. Although many studies evaluated cryptocurrency from the Shariah perspective, they focused only on the Cryptocurrency concept and did not consider the underlying blockchain technology. However, designing a Shariah compliant application on top of a non Shariah compliant platform does not fulfil the requirements of Shariah. Therefore, it is necessary to use a Shariah compliant blockchain platform in order to produce Shariah compliant blockchain applications. To support the production of Shariah compliant blockchain applications, this study provides a comparative analysis of the most used consensus algorithms in blockchain platforms. In particular, the considered consensus algorithms are evaluated from a Shariah perspective. In conclusion, based on the conducted evaluation some of the widely used blockchain platforms (e.g. Bitcoin and Ethereum) are found to be not compliant with the Shariah rules due to using a consensus algorithm that is not Shariah compliant.